The tumor ghost on MRI after microwave ablation for hepatocellular carcinoma: A new modality to assess the ablative margin. Issue 158 (January 2023) - Liu, Sisi; Wu, Jiapeng; Ding, Wenzhen; Zhang, Chaohe; Luo, Yanchun; Bai, Xu; Wen, Ke; Han, Zhiyu; Yu, Jie; Liang, Ping
Abstract: Purpose: The ablated tumor ghost can be visually distinguished on MR images after ablation. This retrospective study aimed to assess the performance of tumor ghost on post-ablation contrast-enhanced MRI with excellular contrast agent gadolinium-DTPA in evaluating the ablative margin of hepatocellular carcinoma (HCC) after microwave ablation (MWA). Method: 315 HCC lesions less than 5 cm in 287 patients completely treated by MWA were enrolled in the study. The tumor ghost was characterized as a lower signal intensity area than the surrounding tissues of the ablation zone on T1WI imaging. The ablation margin (AM) status was classified into AM0 (＞5mm) and AM1 (＜5mm) according to the minimum distance between the tumor ghost and ablated zone. Inter-observer agreement between two radiologists on the AM assessment was analyzed using the Cohen κ coefficient. Multivariate analysis using Cox proportional hazard model was performed to investigate independent risk factors for LTP. Results: 175 and 140 tumors were evaluated as AM0 and AM1 through tumor ghost. The inter-observer agreement level between two radiologists for assessment of AM was good (κ coefficient = 0.752, 95 % confidence interval: 0.679–0.825, p < 0.001). The mediate follow-up period was 32.2 months (range 3.0–60.8 months). The incidence of LTP in the AM0 lesions and AM1 lesions was 6.3 % (11/175) and 20.0 % (28/140), respectively. AM status was identified as an independent prognostic factor for LTP (HR 3.057, 95 % CI, 1.445–6.470, p = 0.003). Conclusions: The assessment of the AM by tumor ghost on post-ablation MRI is an accurate and efficiently method for evaluating the completeness of microwave ablation for hepatocellular carcinoma.